Efficacy and safety of Aflibercept for the treatment of inflammatory choroidal neovascularization: The ALINEA study. Issue 1 (13th July 2022) - Kodjikian, Laurent; Abukhashabah, Amro; Fardeau, Christine; Tadayoni, Ramin; Brézin, Antoine; Dumas, Stéphane; Weber, Michel; Bernard, Lorraine; Loria, Olivier; Decullier, Evelyne; Huot, Laure; Mathis, Thibaud
Abstract: Purpose: To evaluate mean change in best‐corrected visual acuity (BCVA) at 52 weeks in patients with inflammatory choroidal neovascularization (CNV) treated with aflibercept. Methods: We conducted a prospective non‐comparative open‐label trial. Following one mandatory intravitreal injection of aflibercept, patients were treated under a pro re nata (PRN) dosing regimen with monthly visits. Results: A total of 19 patients were included, but one presented exclusion criteria; 16 patients were followed for the whole 52‐week study, and data for the primary endpoint analysis were available for 14. At baseline, mean BCVA and mean central retinal thickness (CRT) were 64.53 (±19.64) letters and 351.79 (±97.77) μm, respectively. At 52 weeks, the mean change in BCVA was +9.50 (±12.90) letters [95%CI = +2.05–+16.95]. One patient had lost more than 15‐letters at 24 weeks, and another one at 52 weeks. CRT change was −62.77 (±100.73) μm at 24 weeks and −66.53 (±97.47) μm at 52 weeks. There was a mean number of 3.56 (±3.29) intravitreal injections at 52 weeks (min = 1; max = 12). No serious ocular adverse events related to the treatment were reported. Conclusions: Our study shows that aflibercept is clinically effective, both anatomically and functionally in the treatment of inflammatory CNV. Following the first injection, the PRN strategy appears sufficient for treating most choroidal neovessels.